Integration of Metagenomic and Stable Carbon Isotope Evidence Reveals the Extent and Mechanisms of Carbon Dioxide Fixation in High-Temperature Microbial Communities - Jennings, Ryan de Montmollin; Moran, James J.; Jay, Zackary J.; Beam, Jacob P.; Whitmore, Laura M.; Kozubal, Mark A.; Kreuzer, Helen W.; Inskeep, William P. (Frontiers in Microbiology, 2017)
Although the biological fixation of CO2 by chemolithoautotrophs provides a diverse suite of organic compounds utilized by chemoorganoheterotrophs as a carbon and energy source, the relative amounts of autotrophic C in chemotrophic microbial communities is not well-established. The extent and mechanisms of CO2 fixation were evaluated across a comprehensive set of high-temperature, chemotrophic microbial communities in Yellowstone National Park by combining metagenomic and stable 13C isotope analyses. Fifteen geothermal sites representing three distinct habitat types (iron-oxide mats, anoxic sulfur sediments, and filamentous ‘streamer’ communities) were investigated. Genes of the 3-hydroxypropionate/4-hydroxybutyrate, dicarboxylate/4-hydroxybutyrate, and reverse tricarboxylic acid CO2 fixation pathways were identified in assembled genome sequence corresponding to the predominant Crenarchaeota and Aquificales observed across this habitat range. Stable 13C analyses of dissolved inorganic and organic C (DIC, DOC), and possible landscape C sources were used to interpret the 13C content of microbial community samples. Isotope mixing models showed that the minimum fractions of autotrophic C in microbial biomass were > 50 % in the majority of communities analyzed. The significance of CO2 as a C source in these communities provides a foundation for understanding community assembly and succession, and metabolic linkages among early-branching thermophilic autotrophs and heterotrophs.